Family Dynamics And Delinquency: Understanding The Experience Of Female Adolescents With Their Families - Melati Sumari; Ida Hartina Ahmed Tharbe; Norsafatul Aznin A. Razak; Norfaezah Md Khalid; Dini Farhana Baharudin (Emerald Publishing Limited, 2024)
Indexed by WOS/Scopus/ERA